2013
DOI: 10.1002/chem.201303734
|View full text |Cite
|
Sign up to set email alerts
|

TiO2–B Nanosheets/Anatase Nanocrystals Co‐Anchored on Nanoporous Graphene: In Situ Reduction–Hydrolysis Synthesis and Their Superior Rate Performance as an Anode Material

Abstract: A unique hybrid, TiO2-B nanosheets/anatase nanocrystals co-anchored on nanoporous graphene sheets, can be synthesized by a facile microwave-induced in situ reduction-hydrolysis route. The as-formed nanohybrid has a hierarchically porous structure, involving both mesopores of approximately 4 nm and meso-/macropores of 30-60 nm in the graphene sheets, and a large surface area. Importantly, electrodes composed of the nanohybrid exhibit superior rate capability (160 mA h g(-1) at ca. 36 C; 154 mA h g(-1) at ca. 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…65-5714), respectively. Anatase TiO 2 may originate from the partial transformation of metastable TiO 2 -B under heating treatment [35][36][37][38] . Refinement results quantify a mass percentage of ca.…”
Section: Resultsmentioning
confidence: 99%
“…65-5714), respectively. Anatase TiO 2 may originate from the partial transformation of metastable TiO 2 -B under heating treatment [35][36][37][38] . Refinement results quantify a mass percentage of ca.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the pristine TiO 2 (B) showed relatively poor sodium storage performances with a rather low specific capacity about 80 mAh g À1 at a specific current of 50 mA g À1 and a specific capacity about 35 mAh g À1 at 400 mA g À1 , which could be attributed to its lower ion diffusion coefficients and worse electronic conductivity (~10 À12 S cm À1 ) [33]. It is found that the inferior electrochemical storage performance for SIBs of pristine TiO 2 is difficult to meet the requirement of practical energy storages [34]. In order to better use its advantages, lots of efforts have been taken to increase its electronic conductivity and avoid the agglomeration of TiO 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 97%
“…[19][20][21][22][23] The enhancement of electrical conductivity and the formation of porous stacking structures upon the hybridization with rGO nanosheets lead to the improvement of their electrode performance at high current density and the accommodation of large volume change during electrochemical cycling. [24][25][26] However, it is not easy to directly hybridize the negatively charged nanosheets of layered metal oxides with isocharged rGO nanosheets due to electrostatic interactions. To overcome this difficulty, it is desirable to modify the negative charge of rGO nanosheets to a positive charge.…”
Section: Introductionmentioning
confidence: 99%